2006
DOI: 10.3904/kjim.2006.21.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Tachycardiomyopathy Induced by Ventricular Premature Complexes: Complete Recovery after Radiofrequency Catheter Ablation

Abstract: Ventricular premature complexes (VPCs) are known to be one of the most benign cardiac arrhythmias when they occur in structurally normal hearts. We experienced a 32-year old man who presented with dyspnea, palpitations and very frequent VPCs (31% of the total heart beats). Echocardiography revealed a dilated left ventricle (LV 66 mm at end-diastole and 57 mm at end-systole) and a decreased ejection fraction (34%). Very frequent VPCs had been detected 10 years previously and he underwent a failed radiofrequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This overexpression of the renin-angiotensin system may account for an individual predisposition to develop cardiomyopathy in the context of incessant tachycardia in some patients. A high burden of ventricular ectopic activity has been shown to result in LV dysfunction (25). In the present study, 1 patient had impaired ventricular function in response to frequent or "incessant" atrial ectopy.…”
Section: Discussionmentioning
confidence: 91%
“…This overexpression of the renin-angiotensin system may account for an individual predisposition to develop cardiomyopathy in the context of incessant tachycardia in some patients. A high burden of ventricular ectopic activity has been shown to result in LV dysfunction (25). In the present study, 1 patient had impaired ventricular function in response to frequent or "incessant" atrial ectopy.…”
Section: Discussionmentioning
confidence: 91%
“…Catheter ablation should be considered as the first-line therapy in all patients with PVC > 20,000/day and LV dysfunction [24]. Still, there are many unclear aspects of tachycardiomyopathy treatment in the prevention of structural changes and long-term risk of sudden cardiac death, which necessitate further exploration [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Premature ventricular complexes (PVCs) are among the most common cardiac arrhythmias encountered in clinical practice. There has been a recent accumulation of evidence implicating PVCs as a cause of reversible cardiomyopathy 1–15 . Many studies have reported the burden of PVCs as a proportion of all ventricular complexes to be a significant determinant of developing left ventricular (LV) systolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a recent accumulation of evidence implicating PVCs as a cause of reversible cardiomyopathy. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Many studies have reported the burden of PVCs as a proportion of all ventricular complexes to be a significant determinant of developing left ventricular (LV) systolic dysfunction. However, a clinically relevant cut-off that identifies an increased risk has not been established.…”
Section: Introductionmentioning
confidence: 99%